Contributions to the millipede fauna of China: five new species of the genus Nepalella Shear, 1979 (Diplopoda, Chordeumatida, Megalotylidae) - Mikhaljova, Elena V. (Zootaxa, 2022)
Five new species of the millipede genus Nepalella Shear, 1979 (Chordeumatida, Megalotylidae) are described from mainland China: N. brevichaeta sp. nov., N. fruticulosa sp. nov., N. labolensis sp. nov., N. shimianensis sp. nov. and N. zhumanica sp. nov. All currently known species of Nepalella are keyed, including the new ones.